PENGARUH SERVICE PERFORMANCE, KEPUASAN, TRUST DAN KOMITMEN TERHADAP LOYALITAS NASABAH DI BANK SYARI’AH MANDIRI KUDUS - Anita Rahmawaty (State Institute of Islamic Studies (IAIN) Salatiga, 2011)
The research is subjected to measure empiric factors that influence onthe consumer loyalities in Bank Syari’ah Mandiri (BSM) Kudus. Therewill be four variables influencing customer loyalities: service performance(serperf), satisfaction, trust and comitment. This reserach is quantitativeresearch with positivistic paradigm. The object of the research is thecustomer of this bank through accidental sampling then Ordinary leastsquare is applied.The finding shows four independent variables but only two of them willinfluence the customer loyalities that are satisfaction and comitment.On the other hands variable of service performance and trust do notinfluence toward customer loyalty. Even that only two variables theAdjusted R2 is 0.727, it means that service performance, satisfaction,trust and commitment could influence customer loyalities for about 72%and the residue of 28% is shown through other variables outside theresearch models. Finally, it could be conclude that the satisfaction andcomitment are important factors that influence customer loyalities ofSyaria bank in Kudus.